Costunolide: A novel anti-cancer sesquiterpene lactone - Rasul, Azhar; Parveen, Saima; Ma, Tonghui (Bangladesh Journal of Pharmacology, 2012)
Currently an ample interest is found among oncologists to explore anticancer compounds from herbs. Sesquiterpene lactones have accredited significant attention in pharmacological research. Costunolide is a well-known sesquiterpene lactone present in plants used as popular herbal remedy. Several plant-derived compounds are currently successfully employed in cancer treatment. Growing evidences demonstrated that costunolide possesses anticancer activities by inhibiting cell proliferation, tumor invasion, angiogenesis, metastasis and inducing apoptosis of a variety of tumor cell lines. This review is aimed to summarize the recent researches about costunolide focusing on anti-tumor activity and to lay emphasis on its molecular targets and its mechanisms, which may help the further design and conduct of preclinical and clinical trials.